The right of asylum in jurisprudence perspective - Nur Syairah Rosman; Hani Nasuha Hamidon; Nabeel Mahdi Althabhawi (Penerbit Universiti Kebangsaan Malaysia, 2023)
The right to asylum is mentioned as one of the human rights in the 1948 Universal Declaration of Human Rights (UDHR) to safeguard those people. When an individual believes that his or her life or freedom may be jeopardized as a result of his or her ethnicity, religion, nationality, participation in a certain social group, or political beliefs, he or she may seek asylum. The purpose of this paper is also to analyse the right to asylum and its international status in addition to asylum cases that occurred in Malaysia. The methodology of this paper is qualitative by reviewing various articles related to the right to asylum. According to the findings, the right to asylum can be granted in two ways internationally: territorial asylum or extra-territorial asylum. The instances also show that more and more countries are agreeing to safeguard asylum seekers. The majority of jurists agreed to grant the seeker the right to asylum. However, a few of those jurists consider that specific conditions must be met to award rights to asylum. As a result, the major outcome of this study is that nations and individuals are becoming more inclined to respect asylum seekers’ rights constantly.